Patient safety culture plays an essential role to ensure safe patient care and quality in healthcare services (Pulse, 2023)
Patient Safety is a global health priority. Every year, millions of patients suffer or die because of unsafe and poor- health care service. There are several factors which compromise patient safety and cause potential harm in health care settings. In developed countries, it is estimated that one in every 10 patients is harmed while receiving care in hospital. In developing countries, there is inadequate information on adverse event due to poor quality of health care service. Despite recent developments in Bangladesh, there is still great concern about the quality of care in healthcare sector. Evercare Hospital Dhaka is one of the leading private health care organizations in the country and committed towards patient safety from the very beginning. The purpose of this article is to discuss the importance of patient safety culture at healthcare service and how it is nurtured at Evercare hospital Dhaka by following the joint commission international standards.Pulse Volume 12-14 2020-2022 p.53-61